Guyana's upper-Mazaruni hydro-electric project : Guyana's answer to a Venezuela representation to the World Bank (Ministry of Economic Planning and Finance GeorgetownGY, 1981)
Presents the letter dated September 19, 1981 from Vice-President Hugh Desmond Hoyte of Guyana to the President of the World Bank answering certain representations made to the Bank by Foreign Minister, Dr. J.A. Zambrano Velasco of Venezuela.
Keywords: BOUNDARIES